Pulmonary vein and left atrial posterior wall isolation for the treatment of atrial fibrillation: Comparable outcomes for adults with congenital heart disease. (14th April 2021) - Moore, Jeremy P.; Gallotti, Roberto; Su, Jonathan; Nguyen, Heajung L.; Bedayat, Arash; Prosper, Ashley; Buch, Eric
Abstract: Introduction: Optimal treatment strategies for ACHD with AF are unknown. This study sought to assess outcomes of pulmonary vein isolation (PVI) ± left atrial (LA), posterior wall isolation (PWI) for adults with congenital heart disease (ACHD), and atrial fibrillation (AF). Methods: A retrospective review of all cryoballoon (CB) PVI ± PWI procedures at a single center over a 3‐year period were performed. Clinical characteristics and outcomes for patients with and without ACHD were compared. The primary outcome was the occurrence of atrial tachyarrhythmia at 12‐months postablation after a 90‐day blanking period. Results: Three‐hundred and sixteen patients (mean: 63 ± 12 years, [63% male]) underwent CB PVI ± PWI during the study, including 31 (10%) ACHD (simple 35%, moderate 39% complex 26%; nonparoxysmal AF in 52%). ACHD was younger (51 vs. 64 years; p < .001) with a lower CHADS2 DS2 ‐VASc score (1.2 vs. 2.1; p = .001) but had a greater LA diameter (4.9 vs. 4.0 cm; p < .001) and a number of prior cardioversions (0.9 vs. 0.4; p < .001) versus controls. 12‐month freedom from recurrent AF was similar for ACHD and controls (76% vs. 80%; p = .6) and remained nonsignificant in multivariate analysis (hazard ratio: 1.8, 95% confidence interval: 0.7–5.1; p = .22). At 12‐months postablation, 75% of ACHD versus 93% of control patients were off antiarrhythmic drug therapy ( p = .07). Conclusion: This study demonstrates younger age and lower conventional stroke risk, yet clinically advanced AF for ACHD relative to controls. CB PVI ± PWI was an effective strategy for the treatment of AF among all forms of ACHD with similar 12‐month outcomes as compared to controls.